2011
DOI: 10.1523/jneurosci.5385-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Development, Maturation, and Necessity of Transcription Factors in the Mouse Suprachiasmatic Nucleus

Abstract: The suprachiasmatic nucleus (SCN) of the hypothalamus is the master mammalian circadian clock. The SCN is highly specialized as it is responsible for generating a near 24-hour rhythm, integrating external cues, and translating the rhythm throughout the body. Currently, our understanding of the developmental origin and genetic program involved in the proper specification and maturation of the SCN is limited. Herein, we provide a detailed analysis of transcription factor (TF) and developmental-gene expression in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
163
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(172 citation statements)
references
References 76 publications
(98 reference statements)
8
163
1
Order By: Relevance
“…The increase in synchrony in the SCN at E15.5 does coincide with Lhx1 expression across the SCN (VanDunk et al, 2011). This transcription factor is important for the expression of diverse neuropeptide coupling signals aside from VIP, such as GRP or AVP (Bedont et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The increase in synchrony in the SCN at E15.5 does coincide with Lhx1 expression across the SCN (VanDunk et al, 2011). This transcription factor is important for the expression of diverse neuropeptide coupling signals aside from VIP, such as GRP or AVP (Bedont et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Inclusion of these extra-SCN regions in explants could explain the discrepancy between the two studies that reported the onset of PER2 daily oscillations in hypothalamic explants at E13 or E15 (Wreschnig et al, 2014;Landgraf et al, 2015). Importantly, the correlations in the increasing fraction of rhythmic cells, increasing circadian period and increasing inter-and intracellular period precision during this time could reflect the consequences of cell-cell communication (Webb et al, 2009) and/or maturation of molecular components for circadian rhythm generation (VanDunk et al, 2011;Ono et al, 2016). Previous studies demonstrated that embryonic SCN have a strong phase-setting in response to perturbations such as surgical isolation (Wreschnig et al, 2014;Landgraf et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…ISH ISH was performed as described previously (VanDunk et al 2011) on coronal sections of P28 wild-type mouse brains that were immersion-fixed in 4% paraformaldehyde for 20 min and cryoprotected in sucrose before sectioning. Digoxigenin-labeled riboprobe was transcribed with T7 RNA polymerase using the templates described (Supplemental Table S3).…”
Section: Anatomical Analysismentioning
confidence: 99%
“…Cell cultures were fixed and stained with modifications protocol from previously described [25][26][27]. Cell cultures were fixed in 4% PFA for 10 min and washed thrice in diethylpyrocarbonate (DEPC; Sigma)-treated PBS at room temperature.…”
Section: In Situ Hybridizationmentioning
confidence: 99%